UPAYA PENINGKATAN PRAKTIK PENGAJARAN BAHASA ARAB PERSPEKTIF DOSEN DI IAI SHALAHUDDIN AL-AYYUBI - miftahul huda; Faishol Hakim; Hawasi Arsam; Kerwanto (LPPM Institut Nida El-Adabi, 2025)
Teaching Arabic in Indonesia plays an important role in Islamic education, yet its implementation often encounters various challenges. This study aims to analyze the difficulties faced by lecturers in teaching Arabic at the Shalahuddin Al-Ayyubi Institute of Islamic Studies and to formulate solutions for improving the quality of instruction. Using a qualitative approach through interviews, classroom observations, and document analysis, the study identifies several issues, including limited teaching resources, less effective teaching methods, and low levels of interaction between lecturers and students. The findings also highlight the need to integrate technology and interactive methods, as students respond more positively to such approaches. Based on these results, the study recommends curriculum development and lecturer training to enhance teaching practices. These findings are expected to serve as a reference for improving the quality of Arabic language education at the institution.